2023
DOI: 10.1039/d2bm01369j
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose-based hydrogels towards an antibacterial wound dressing

Abstract: Hydrogels are candidates for wound healing bandages because they can mimic the native skin microenvironment. Additionally, there is an increasing growth in the use of naturally derived materials and plant-based...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…The antibacterial properties of I 2 /HP-β-CD hydrogel (Gel 1), Schiff base hydrogel (Gel 2), and DAC hydrogel (Gel 3) were tested by Oxford ring diffusion assay and plate counting assay . Experimental procedures are available in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…The antibacterial properties of I 2 /HP-β-CD hydrogel (Gel 1), Schiff base hydrogel (Gel 2), and DAC hydrogel (Gel 3) were tested by Oxford ring diffusion assay and plate counting assay . Experimental procedures are available in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…Guamba et al made hydrogels from cellulose extracted from pear exocarp, tomato, and dragon fruit, and the results of in vitro antibacterial activity tests showed that the hydrogels of the fiber samples tomato and dragon fruit inhibited the growth of bacteria. [241] Sun et al fibrously investigated a novel cellulose-based supramolecular self-assembled hydrogel (Gel-(𝛽)CDP-HEC), which was formed based on the host-guest interaction between hydrophobic hydroxyethyl cellulose dodecyl side chains (HEC-C 12 ) and cavities in polycyclodextrin (𝛽-CDP).Gel-(𝛽)CDP-HEC hydrogel material showed Escherichia coli with strong long-term antibacterial activity. [242] Wu et al prepared a double cross-linked self-healing antimicrobial nanocellulose gel for human motion monitoring that can periodically sense motion signals when the hydrogel is immobilized on the human wrist, validating the potential of hydrogels in the development of next-generation wearable products (Figure 19c).…”
Section: Biomedical Potential Of Natural Macromolecular Antibacterial...mentioning
confidence: 99%
“…[243] Guamba et al prepared a cellulose-based hydrogel for use as an antimicrobial wound dressing(Figure 19d). [241] However, the antimicrobial properties of cellulose hydrogels are derived from the electrostatic force between cellulose and bacteria, which is far from sufficient to cope with serious infections, and its hydrogel modification modification or its combination with other therapeutic methods is needed to improve the antimicrobial activity. For example, Arellano-Sandova et al functionalized agave xylanbased hemicellulose with trimethoxysilyl methacrylate and crosslinked with N-vinylcaprolactam to obtain temperature-sensitive The schematic demonstration for the preparation of the hydrogel and its potential application for cutaneous wound healing.…”
Section: Biomedical Potential Of Natural Macromolecular Antibacterial...mentioning
confidence: 99%
See 2 more Smart Citations